2018
DOI: 10.1186/s12902-018-0236-4
|View full text |Cite
|
Sign up to set email alerts
|

FSH may be a useful tool to allow early diagnosis of Turner syndrome

Abstract: BackgroundUltrasensitive assays to measure pre-pubertal gonadotropins levels could help identify patients with Turner syndrome (TS) in mid-childhood, but studies in this field are scarce. The aim of this study was to analyze gonadotropins levels in girls with TS throughout childhood.MethodsRetrospective longitudinal study conducted with 15 girls with TS diagnosed with < 5 years whose FSH and LH measures were available since then. Hormones were evaluated in newborn/mini-puberty (< 0.5 years), early childhood (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…This is seen most profoundly in individuals with gonadal dysgenesis who have high concentrations of LH and FSH during infancy and adolescence. 25,26 In healthy females, positive feedback by estradiol also occurs from mid-puberty onwards, a process that is necessary for ovulation.…”
Section: Sex Steroid Feedback On the Hypothalamus And Pituitarymentioning
confidence: 99%
“…This is seen most profoundly in individuals with gonadal dysgenesis who have high concentrations of LH and FSH during infancy and adolescence. 25,26 In healthy females, positive feedback by estradiol also occurs from mid-puberty onwards, a process that is necessary for ovulation.…”
Section: Sex Steroid Feedback On the Hypothalamus And Pituitarymentioning
confidence: 99%
“…Hypogonadism is the result of a massive apoptosis of the oocyte pool occurring from fetal life to late childhood (59). A retrospective longitudinal study (60) analyzed FSH and LH levels at different ages in 15 girls with Turner syndrome. Four out of 5 patients whose gonadotropins were measured during minipuberty had abnormally high FSH levels, none of them entered spontaneous puberty.…”
Section: Lessons From Genetic Disorders/differences Of Sex Developmenmentioning
confidence: 99%
“…LH secretion was also biphasic, but only 1 girl showed remarkably high LH concentration in the first 6 months of life, while LH levels increased from late childhood to adolescence. It has been suggested that FSH measurement could be helpful for the early detection of Turner syndrome in infants with suggestive signs, especially in settings with limited resources for karyotype analysis (60).…”
Section: Lessons From Genetic Disorders/differences Of Sex Developmenmentioning
confidence: 99%
“…46 To make a preliminary TS diagnosis, several studies look at typical clinical features at various periods of life. For example, cystic hygroma, diffuse edema, and development retardation present in female foetuses 7 ; new-born having webbed neck and congenital lymphedema in the feet and hands during birth 8 ; high follicle-stimulating hormone intensities and short height in children 9 ; short height or/and primary amenorrhea present in adolescents; ovarian failure in adults 10 ; are patients alleged to be having TS that must be highlighted. Nevertheless, in actual reality, the aforesaid TS screening methods need multiple physicians using extensive clinical expertise that are in short supply in impoverished cities and rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Finer Energy Features (FEF) beats further four feature sets, wherein the classifier created using weighted voting technique obtains the best accuracy of 0.9127. Children with short height and elevated follicle-stimulating hormone points are characterized by Carpini et al 9 In order to retrieve bone age for ultimately reaching measurements set, image processing procedures like subtraction of background, elimination of noise and recognition of soft tissue has endured numerous revisions according to Simu and Lal. 17 Maji outlines the manner in which merging and region-growing techniques are based on the similarity 18 metric and connection, 19 which might result in the epiphysis sites being fused.…”
Section: Introductionmentioning
confidence: 99%